2018
DOI: 10.1159/000485896
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Allergen Sensitization Patterns of Patients with Local Allergic Rhinitis in Southern China

Abstract: Background: Local allergic rhinitis (LAR) is characterized by the production of specific IgE (sIgE) in the nasal mucosa without evidence of systemic atopy. The characteristics of LAR in Caucasians have been well documented. LAR is understudied in China, with prevalence, patient demographics, symptomatology, and the allergen sensitization profile being poorly understood. The purpose of this study is to investigate the demographics, characteristics, and allergen sensitization profile of patients with LAR in Sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 11 publications
1
21
0
2
Order By: Relevance
“…Nevertheless, the existing literature reflects an extremely wide range of LAR prevalence among non-atopic rhinitis patients (0–100%) [9,21,22,23,24,26,27,28,29,30,31,32,33,34,37]. In recent years, several studies from Asian countries have become available and overall report a lower (<20%) prevalence of LAR as compared to Western countries [26,27,29,33,37]. It has been suggested that LAR prevalence in the Mediterranean areas (Portugal, Spain, Italy, Greece, etc.)…”
Section: Epidemiologymentioning
confidence: 99%
“…Nevertheless, the existing literature reflects an extremely wide range of LAR prevalence among non-atopic rhinitis patients (0–100%) [9,21,22,23,24,26,27,28,29,30,31,32,33,34,37]. In recent years, several studies from Asian countries have become available and overall report a lower (<20%) prevalence of LAR as compared to Western countries [26,27,29,33,37]. It has been suggested that LAR prevalence in the Mediterranean areas (Portugal, Spain, Italy, Greece, etc.)…”
Section: Epidemiologymentioning
confidence: 99%
“…In this regard, a systematic review concluded that 16% of non-atopic children with rhinitis fulfill diagnostic criteria for LAR ( 19 ). Nevertheless, regional differences in LAR prevalence might exist, as published data consistently identify a higher frequency of LAR among Western (29-67%) ( 20 23 ) as compared to Asian (0-19%) ( 24 27 ) non-atopic children with rhinitis. To address this aspects, we recently conducted a systematic evaluation (SPT, serum sIgE and NAC) of pediatric patients referred to specialized units for chronic nasal symptoms, and found a 46%, 12%, 25% and 18% prevalence for AR, DAR, LAR and NAR, respectively ( 18 ).…”
Section: Local Respiratory Allergy Across the Lifespanmentioning
confidence: 99%
“…Dust mites are a common trigger for AR [10]. The prevalence of house dust mites (HDMs) in AR patients in southern China is 95% [11]. Avoiding allergen exposure is an important measure to treat AR.…”
Section: Background and Rationalementioning
confidence: 99%